Practice and perception–a nationwide survey of therapy habits in sepsis - Brunkhorst, Frank M.; Engel, Christoph; Ragaller, Max; Welte, Tobias; Rossaint, Rolf; Gerlach, Herwig; Mayer, Konstantin; John, Stefan; Stuber, Frank; Weiler, Norbert; Oppert, Michael; Moerer, Onnen; et al. (Critical care medicine, 2008)
OBJECTIVE To simultaneously determine perceived vs. practiced adherence to recommended interventions for the treatment of severe sepsis or septic shock. DESIGN One-day cross-sectional survey. SETTING Representative sample of German intensive care units stratified by hospital size. PATIENTS Adult patients with severe sepsis or septic shock. INTERVENTIONS None. MEASUREMENTS AND MAIN RESULTS Practice recommendations were selected by German Sepsis Competence Network (SepNet) investigators. External intensivists visited intensive care units randomly chosen and asked the responsible intensive care unit director how often these recommendations were used. Responses \textquotedblalways\textquotedbl and \textquotedblfrequently\textquotedbl were combined to depict perceived adherence. Thereafter patient files were audited. Three hundred sixty-six patients on 214 intensive care units fulfilled the criteria and received full support. One hundred fifty-two patients had acute lung injury or acute respiratory distress syndrome. Low-tidal volume ventilation < or = 6 mL/kg/predicted body weight was documented in 2.6% of these patients. A total of 17.1% patients had tidal volume between 6 and 8 mL/kg predicted body weight and 80.3% > 8 mL/kg predicted body weight. Mean tidal volume was 10.0 +/- 2.4 mL/kg predicted body weight. Perceived adherence to low-tidal volume ventilation was 79.9%. Euglycemia (4.4-6.1 mmol/L) was documented in 6.2% of 355 patients. A total of 33.8% of patients had blood glucose levels < or = 8.3 mmol/L and 66.2% were hyperglycemic (blood glucose > 8.3 mmol/L). Among 207 patients receiving insulin therapy, 1.9% were euglycemic, 20.8% had blood glucose levels < or = 8.3 mmol/L, and 1.0% were hypoglycemic. Overall, mean maximal glucose level was 10.0 +/- 3.6 mmol/L. Perceived adherence to strict glycemic control was 65.9%. Although perceived adherence to recommendations was higher in academic and larger hospitals, actual practice was not significantly influenced by hospital size or university affiliation. CONCLUSIONS This representative survey shows that current therapy of severe sepsis in German intensive care units complies poorly with practice recommendations. Intensive care unit directors perceive adherence to be higher than it actually is. Implementation strategies involving all intensive care unit staff are needed to overcome this gap between current evidence-based knowledge, practice, and perception.